Unveiling the Influencers of Online Shopping Intentions: A Case Study of Public University Students in Chengdu, China - Fang, Niu (Scholar: Human Sciences, 2025)
Purpose: This study investigates the determinants influencing students’ inclination to online shopping at a public university in Chengdu, China. The research framework is constructed upon attitude, subjective norm, perceived behavioral control, positive anticipated emotion, negative anticipated emotion, tech readiness, and desire. Research design, data, and methodology: The study focused on a population and sample size of 500 students who have engaged in online shopping for at least one semester from public universities in Chengdu, China. Various sampling techniques were employed to gather data, including judgmental, quota, convenience, and snowball sampling. Questionnaires were used as the primary instrument for data collection from the target population, with distribution conducted among undergraduates in three selected universities in Chengdu, China. Data analysis involved using the Structural Equation Model (SEM) and Confirmatory Factor Analysis (CFA) to assess model fit, reliability, and validity of constructs. Results: The findings indicated that attitude, subjective norm, tech readiness, behavioral intention, and desire significantly influence online shopping behavior. Seven hypotheses were supported, suggesting that attitude, behavioral intention, and desire are crucial in assessing influencers and intentions to enhance online shopping behavior. Conclusion: The research findings suggest that positive anticipated emotions have a strong impact on online shopping intentions, although this influence may decrease over time. Negative anticipated emotions, such as dissatisfaction and unhappiness, also affect online shopping behavior.